2016
DOI: 10.5213/inj.1630478.239
|View full text |Cite
|
Sign up to set email alerts
|

Holmium Laser Enucleation of the Prostate is Safe for Patients Above 80 Years: A Prospective Study

Abstract: Purpose:To evaluate the effect of age on the efficacy and safety of holmium laser enucleation of the prostate (HoLEP) for the treatment of symptomatic benign prostatic hyperplasia (BPH).Methods:A total of 579 patients underwent HoLEP procedure performed by a single surgeon (SJO) between December 2009 and May 2013. The perioperative and functional outcomes of patients in the age groups of 50–59 (group A, n=44), 60–69 (group B, n=253), 70–79 (group C, n=244), and ≥80 years (group D, n=38) were compared. The Clav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 12 publications
0
40
0
3
Order By: Relevance
“…Holmium laser enucleation of the prostate (HoLEP) makes it possible to remove an entire enlarged adenoma confidently in the natural-tissue plane of the surgical capsule. A recent study reported that HoLEP is a safe and effective treatment for benign prostatic hyperplasia (BPH) among the elderly [ 1 ]. Compared with younger patients, patients aged ≥80 years had similar overall morbidity and 6-month functional outcomes after HoLEP [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holmium laser enucleation of the prostate (HoLEP) makes it possible to remove an entire enlarged adenoma confidently in the natural-tissue plane of the surgical capsule. A recent study reported that HoLEP is a safe and effective treatment for benign prostatic hyperplasia (BPH) among the elderly [ 1 ]. Compared with younger patients, patients aged ≥80 years had similar overall morbidity and 6-month functional outcomes after HoLEP [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that HoLEP is a safe and effective treatment for benign prostatic hyperplasia (BPH) among the elderly [ 1 ]. Compared with younger patients, patients aged ≥80 years had similar overall morbidity and 6-month functional outcomes after HoLEP [ 1 ]. Thus, HoLEP is considered a safe and effective treatment modality for bladder outlet obstruction (BOO) related to BPH, and has been reported to have lower morbidity rates than other modalities [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…All operations were performed using a holmium: yttrium-aluminum-garnet laser by two surgeons (SJO and JKO). The holmium laser apparatus used in our study were OmniPulse (Trimedyne Inc., Irvine, CA, USA) and VersaPulse PowerSuite (Lumenis, Yokneam, Israel) [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…A prospective study by Piao et al stratified patients into 4 age groups identical to those used by Mmeje et al (Piao, Choo, Kim, Jeon, & Oh, 2016). Despite patients 80 years and older having significantly higher American Society of Anaesthesiologists scores and rates of anticoagulation use, longer operating times and greater enucleation weights, the incidence of complications was similar across the groups.…”
Section: Outcomes Independent Of Patient Agementioning
confidence: 99%